HIPERURISEMIA SEBAGAI FAKTOR RAMALAN PERJALANAN PENYAKIT (PROGNOSIS) GEJALA KLINIK STROK INFARK - Fenty .; Harjo Mulyono; Siti Muchayat (Indonesian Association of Clinical Pathologist and Medical laboratory, 2010)
Infarction stroke is a leading cause mortality and disability in the world. Appropriate management of acute infarction stroke will be able to reduced morbidity and mortality of the disease. Many laboratory parameters which can be done for detecting risk of prognosticfactors, one of them is serum uric acid concentration. The aim of this study is to know if hyperuricemia is prognostic factor for clinicaloutcome in acute infarction stroke.A prospective cohort study was carried out, compare between two groups of exposed and non-exposedgroup. Subjects who meet inclusion and exclusion criteria was involved in the study. The exposed group was a group of acute infarctionstroke patients who exposed to hyperuricemia, in other hand, patient who do not have hyperuricemia was separated as the non-exposedgroup. Inception cohort was applied when patient admits to emergency unit during 48 hours of onset, age ≥ 40 years old, man orwoman, have signed informed consent are inclusion criteria. Gadjah Mada Stroke Scale and serum uric acid concentration was measured on admission. Patient with haemorhage stroke and who are taking medicine that cause decrease uric acid are excluded. Test of serum uric acid concentration was performed by using Vitros 250, dry chemistry system. Patients were followed up 7 days in Neurology Unitand the outcome were measured by evaluating a score of Gadjah Mada Stroke Scale. Prognostic factor hyperuricemia has RR= 2.159(95% CI: 0.684-6.816), p= 0.158 for outcome. Hyperuricemia is not be evident as prognostic factor in acute infarction stroke.